(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article contains an analysis of the results of research of the development of the tractor and combine fleet in Latvia in 2014-2023. The age structure and technical condition of the tractor fleet have been determined. More than 100 thousand tractors and 9.5 thousand combines are registered in the country. More than 100 thousand tractors and 9.5 thousand combines are registered in Latvia. 32.2% of tractors are in good technical condition, 71% of tractors are over 30 years old, only 10.8% fall into the age group of up to 15 years, which is usually considered the depreciation period. Combine harvester fleet is in a similar technical condition. The current registration procedure of the tractor equipment - without excluding the obsolete and worn-out equipment from the register - does not provide an impartial impression of the technical condition of the tractor equipment fleet, the performance of the fleet and the energy supply to agriculture. During the period an average of 462 new tractors with a power exceeding 100 HP and 130 new harvesters were purchased annually. Using the available registry data about the capacity and year of registration of tractors and combines, the total capacity of the fleet by year was calculated. To ensure depreciation of the tractor equipment that has been in operation for more than 15 years, the calculated capacity has been reduced by 15%, but increased by 10%, which approximately corresponds to the area, cultivated by the equipment that is more than 15 years old. The calculated total capacity is compared with the cultivated area in the corresponding year. It has been established that during the period the total capacity of the tractor fleet has increased by 35%, and the sown area by 13%, so the increase in capacity significantly outpaces the increase in the sown area, which allows the work to be carried out in shorter agrotechnical terms. The capacity of the combine harvester fleet has also increased similarly. It is expected that the total capacity of the tractor equipment will continue to grow at a similar pace. Since the growth rate of the sown areas will decrease in the future, the issue of the amount of subsidies for the purchase of the new tractor equipment is debatable.